2021
DOI: 10.3390/en14020263
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Delignification and Microstructural Characterization of Switchgrass

Abstract: This present study was undertaken to investigate the ultrasonic delignification of switchgrass (Panicum virgatum L.) and the effects of ultrasonic irradiation on the molecular and microstructure of switchgrass. We investigated this question using response surface methodology (RSM) featuring a four-factor, three-level Box–Behnken experimental design with acoustic power (120, 180, and 240 W), solid–solvent ratio (1/25, 1/20, and 1/15 g/mL), hammer mill screen size (1.6, 3.2, and 6.4 mm), and sonication time (10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 54 publications
(74 reference statements)
1
11
0
Order By: Relevance
“…As found, term 𝑥𝑥 1 𝑥𝑥 2 𝑥𝑥 4 2 in the equation had the largest coefficient, indicating that a high ultrasonic power was suitable to increase bio-H2 production. These results were in line with those reported in the literature (Gadhe et al 2014;Arun and Sivashanmugam 20018;Olughu et al 2021). They reported that the ultrasonic pretreatment effectively enhances the biodegradability of complex materials, and thus, favors increased biohydrogen recovery.…”
Section: Fig 4 Biohydrogen Productionsupporting
confidence: 92%
“…As found, term 𝑥𝑥 1 𝑥𝑥 2 𝑥𝑥 4 2 in the equation had the largest coefficient, indicating that a high ultrasonic power was suitable to increase bio-H2 production. These results were in line with those reported in the literature (Gadhe et al 2014;Arun and Sivashanmugam 20018;Olughu et al 2021). They reported that the ultrasonic pretreatment effectively enhances the biodegradability of complex materials, and thus, favors increased biohydrogen recovery.…”
Section: Fig 4 Biohydrogen Productionsupporting
confidence: 92%
“… Pretreatment Method Lignocellulosic biomass Optimized reaction Conditions Delignification (%) Reference Ultrasound + alkali Sugarcane bagasse 400 W power, 24 kHz Frequency, 100% duty cycle, time 50 min, 70˚C temperature, 1 M alkali concentration 92 [5] Only US switchgrass Power 180 W, Frequency 24 kHz, time 50 min, Solvent used as distilled water, 90% duty cycle. 21 [54] Only Alkaline Pretreatment Sugarcane bagasse 1 N alkali concentration, 100˚C temperature, 1 bar pressure, Time 45 min. 58 [55] US + Alkali pretreatment News paper 100 W power, 20 kHz frequency, 1 alkali concentration, 80% Duty cycle, 70 min time, 80 ˚C temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Among the independent variables considered in this study, the hammer mill screen size showed no significant impact on any of the response variables. This could be connected to the slight differences in the geometric mean diameter of the switchgrass grind milled with the different hammer mill screen sizes selected in this study, as reported in a previous study [29]. However, the interaction effect of the hammer mill screen size and inoculum concentration on the pellet unit density and tensile strength of pellets from PC-and TV52J-pretreated switchgrass was statistically significant.…”
Section: Effects Of Independent Variables and Their Interactions On The Switchgrass Pellet Qualitymentioning
confidence: 47%
“…The switchgrass samples collected were pre-chopped and stored in plastic bags. The switchgrass samples were comminuted using a hammer mill to three different screen sizes (6.4, 3.2 and 1.6 mm) and then stored in air-tight polyethylene bags as described in our previous study [29].…”
Section: Feedstockmentioning
confidence: 99%
See 1 more Smart Citation